BIOACTIVE COMPOUNDS AND ANTIOXIDANT ACTIVITY DURING FOOD PROCESSING OF BEET STALKS AND LEAVES (Beta vulgaris L.) - Lorizola, Isabela Micheletti; Crivelin, Vitor Xavier; Bezerra, Rosângela Maria Neves; Ferla, Luane Freitas; Francischini, Nathália Valim; Machado, Luciene Lauer; Capitani, Caroline Dário (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2020)
We assessed the effect of cooking methods (baking and steaming) on the phytochemicals and antioxidant activity of aqueous and ethanolic extracts of beet (Beta vulgaris L.) stalks and leaves using FRAP and DPPH assays. Steaming for 45 minutes increased (p < 0.05) the concentration of phenolic compounds compared to raw beet stalks and leaves. In contrast, we observed a reduction of these compounds (p < 0.05) when beet leaves and stalks were baked. The type of solvent used to prepare the extracts also influenced the concentration of phytochemicals and antioxidant activity. The ethanolic extract was more efficient in extracting phenolic compounds from the steamed samples and yielded the highest antioxidant values measured by the DPPH assay (p < 0.05).. The results suggest that beet leaves and stalks should be consumed after steaming. This vegetable can contribute to phenolic compounds in a balanced diet, contributing to the reduction of food waste.